Analisis Kualitas Website SMK Negeri 2 Sragen dengan Metode Webqual 4.0 dan Importance Performance Analysist (IPA) - Pamungkas, Ridwan Aji; Alfarishi, Excel; Aditiarna, Erdian; Muklhisin, Anang; Alfa Aziza, Rifda Faticha (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2019)
The website is one of many communication media that contains information in the form of text, sound, images, or videos that can be accessed publicly by the public. Measurements and observations are made to determine the quality of a website. By doing this, we can understand the opinions of users on a website. The implementation of this study uses a combined method, namely the Webqual method as the main reference with indicators of usability, information quality, and service interactions and Importance Performance Analysis (IPA) methods. The target location taken in this study was the environment of SMK Negeri 2 Sragen. To get data accurately from end users, data collection is used by questionnaire method. The scope of the object to be studied is Students of SMK Negeri 2 Sragen. The results that will be obtained after the research are the development of website usability for users who access it. Other things such as appearance and service provided are the main factors towards user satisfaction in using the website of SMK Negeri 2 Sragen.